Exploring financial literacy as a mediator in the theory of planned behavior on senior citizens’ reverse mortgage purchase intentions - Choudhary, Renu; Santram, Taank Jyoti (The Economics and Finance Letters, 2025)
The increasing population in India necessitates implementing measures to ensure financial stability during their retirement years. A reverse mortgage is a very effective and unique option that allows senior citizens to transform the value of their home equity into a reliable source of income. This study examines the decision-making process of elderly individuals in India regarding reverse mortgage loans using the robust framework of the Theory of Planned Behavior (TPB). This study investigates the impact of the essential characteristics of the TPB model and the mediator role of financial literacy on the intention of older citizens to purchase reverse mortgage loans. The study highlights the lack of understanding among senior personnel regarding financial decisions about adopting reverse mortgages in their old age, specifically concerning their homes by formulating a hypothesis. The study intends to provide significant information to policymakers and financial institutions by examining the role of financial literacy as a mediator within the constructs of the TPB model. Furthermore, the findings enhance the condition of elderly individuals guiding policymakers on improving the range of products and services available to them, implementing a comprehensive strategy for making educated financial decisions and initiating financial literacy programs tailored explicitly for senior residents in India. Therefore, a reverse mortgage is the most suitable choice to ensure a stress-free retirement for elderly individuals in India as it can grant them financial stability and empowerment throughout their later years.